A new education of women. Denis Diderot’s anatomy course project for young noble women - Forycki, Maciej (Biuletyn Historii Wychowania, 2013)
A new education of women. Denis Diderot’s anatomy course project for young noble women. Denis Diderot (1713–1784) explained how women’s education should be different than before. A woman should be considered a citizen, Diderot demanded placing primary social importance on her domestic activity. An interesting feature of this new approach to education of women was to include an anatomy course in their personal development. Denis Diderot did not devote a separate tractate to the issue of women’s education, nor did he write a concise curriculum in anatomy. However, the remarks scattered among various texts by the philosopher concerning that innovative concept allow us not only to reconstruct a fairly cohesive draft of an anatomy course for girls, but also superbly illustrate Diderot’s commitment to realization of his own ideas. Secondly, we need to consider the activities of one Ms. Biheron – the organizer of public anatomy courses – which exerted, as we will see, a huge influence on Diderot’s conviction of the need to incorporate such courses in women’s education. In the last part of the discourse, the involvement of the French philosopher in the educational reforms of Catherine II should be noted. The analysis of Diderot’s texts on education clearly indicates that the philosopher put a strong emphasis on changes in the methods of teaching women. As the director of St. Petersburg facility for girls he managed to partially put his project into effect. Of course, for French philosophers – blind to Russian realities – the unquestionable success of Diderot’s anatomy course might be another argument for the proclamation of the view that Catherine II realized in her country the postulates of the Enlightenment.